Proteomic Analysis of Whole Saliva in Relation to Dental Caries Resistance - Kulhavá, L; Eckhardt, A; Pataridis, S; Foltán, R; Mikšík, I (Folia biologica, 2020)
Saliva contains possible biomarkers that are associated with dental caries. The present study aimed to analyse differences in the abundance of proteins in the saliva between caries-positive (CP; N = 15) and caries-free (CF; N = 12) males and to compare differences in the abundance of proteins between two saliva sample fractions (supernatant and pellet). We found 14 differently significantly expressed proteins in the CF group when comparing the supernatant fractions of the CP and CF groups, and three proteins in the pellet fractions had significantly higher expression in the CP group. Our results indicate very specific protein compositions of the saliva in relation to dental caries resistance (the saliva of the CP group mainly contained pellet proteins and the saliva of the CF group mainly contained supernatant proteins). This was the first time that the saliva pellet fraction was analysed in relation to the dental caries status. We detected specific calcium-binding proteins that could have decalcified enamel in the saliva pellet of the CP group. We also observed significantly up-regulated immune proteins in the saliva supernatant of the CF group that could play an important role in the caries prevention. The particular protein compositions of the saliva pellet and supernatant in the groups with different susceptibilities to tooth decay is a promising finding for future research.
Keywords: Humans; náchylnost k zubnímu kazu; Dental Caries; Saliva; zubní kaz; mužské pohlaví; Male; Dental Caries Susceptibility; Proteomics; sliny; lidé; proteomika; slinné proteiny a peptidy; Salivary Proteins and Peptides